Analisis Pengaturan tentang Pemberhentian Antar- Waktu (Recall) Partai Politik terhadap Status Keanggotaan Dewan Perwakilan Rakyat Menurut Sistem Kedaulatan Rakyat - Indirwan, Indirwan; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThis research describes and examines issues related to the implementation of the recall right of political parties to the existing membership status of the DPR and the correlation between the recall right of political parties to the membership of the DPR and the people’s sovereignty system in the 1945 Constitution of the Republic of Indonesia. This research is a type of normative legal research. The legal source used consists of primary and secondary legal materials obtained through library studies.Legal material analysis technique is to analyze the results of research and discussion using the theories contained in the literature review. The results showed that the right of recall from 1966 to 2009 as well as the positive law that is currently in accordance with the mandate given by the law, only caused problems in one of the reasons for intermission that is based on violations of the AD/ART party. Thecorrelation between the recall rights of political parties and the people’s sovereignty system is not in line with the electoral system with the position of political parties in representative institutions, then the recall rules are also not in accordance with the principles of sovereignty.Keywords : member of DPR; political party; sovereignty; recall.